Integration of Islamic Sciences and Secular Sciences Through Spiritualization and Humanization Approaches - Ilyas Supena (Hikmatuna : Journal for Integrative Islamic Studies, 2022)
The integration of science and religion is a topic of heated debate in the Western world. Ian G Barber describes this relationship between science and religion in terms of conflict, independence, dialogue, and integration. The theme of the relation between science and religion is not only a hot topic in the Western world, it has also attracted the attention of several contemporary Muslim thinkers. Unfortunately, in the discourse of Islamic sciences, the object of debate is more on criticism of secular science so that it needs to be Islamized, whereas at the same time, Islamic sciences also have serious internal problems. Using qualitative research methods by exploring authoritative text sources, this paper aims to offer a balanced perspective in viewing Western science and Islamic science. This research shows that both Western science and Islamic science have weaknesses. Western science is seen as secular science so that it loses its divine vision, while Islamic science is theocentric so that it loses its humanist vision. This finding has implications for different strategies in dealing with the two types of knowledge. Spiritualization is a strategy relevant to Western science, while humanization is a strategy relevant to Islamic sciences.